Selective monitoring of insulin secretion after CRISPR interference in intact pancreatic islets despite submaximal infection. Issue 3 (3rd May 2020) - Shariati, Kaavian; Pappalardo, Zachary; Chopra, Deeksha G.; Yiv, Nicholas; Sheen, Robin; Ku, Gregory
ABSTRACT: Virus-mediated gene knockdown in intact pancreatic islets is technically challenging due to poor infection of the center of the islet. Because the cells that do not have knockdown have normal insulin secretion, measuring changes in insulin secretion after gene knockdown is challenging. We describe a method to monitor insulin secretion from only the beta cells with knockdown of a gene of interest in intact islets using a single lentivirus containing a guide RNA, a luciferase insulin secretion reporter and a dCas9-KRAB cassette. This method allows rapid and inexpensive monitoring of insulin secretion from only those beta cells with knockdown, circumventing the problem of incomplete islet infection.